Symbolic Legitimacy Without Elections: A Computational Framing Analysis of the Bureaucratic Branding Practices of Non-Elected Officials on Social Media (Case Study of Teddy Indra Wijaya) - Rizky Saputra; Andri Yoga Pratama; Edison Bonartua Hutapea (Jurnal Indonesia Sosial Sains, 2026)
This study analyzes the phenomenon of bureaucratic branding on non-electoral officials in the context of digital political communication in Indonesia through a case study of the "Teddy Effect." The main objective of the study is to identify how symbolic legitimacy can be formed outside of electoral mechanisms through the construction of digital narratives on social media. This study uses a mixed-methods approach with an explanatory sequential design, which integrates computational content analysis and qualitative framing analysis. The research data consists of 20,317 text units covering 197 posts from the official account @teddy_hq and 20,120 audience comments on Instagram and TikTok platforms during the period of November 2025 to June 2026. The analysis techniques used include IndoBERT-based sentiment analysis, topic modeling with Latent Dirichlet Allocation (LDA), framing analysis based on the Entman model, and network analysis to map digital interaction patterns. The results of the study indicate that symbolic legitimacy is formed through three main stages in the Digital Bureaucratic Branding (DBB) model, namely symbolic capital (military, loyalty, and competence), digital image construction mechanisms (self-presentation, framing, parasocial, and algorithmic amplification), and output in the form of legitimacy without an electoral mandate. The findings also indicate the dominance of parasocial political relationships and frames of management recommendations that indicate the granting of a "virtual mandate" by the audience. In conclusion, this phenomenon extends the concept of political branding to the non-electoral bureaucratic realm and shows that political legitimacy can be constructed symbolically through digital media without involving electoral mechanisms.